Detail view of glass spinning cell (1937)
Detail view of a glass spinning cell used during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. In this design, the nylon polymer was melted in the glass chamber visible at the center of the photograph, which allowed researchers to study bubbles in the melt resulting from the decomposition of the polymer.
Keywords: Nylon; Scientific apparatus and instruments; Polymers; Nylon--Testing; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Machinery